Effects of Ozone Water Combined With Ultra-High Pressure on Quality and Microorganism of Catfish Fillets (Lctalurus punctatus) During Refrigeration - Ling, Yuzhao; Zhou, Mingzhu; Qiao, Yu; Xiong, Guangquan; Wei, Lingyun; Wang, Lan; Wu, Wenjin; Shi, Liu; Ding, Anzi; Li, Xin (Frontiers in Nutrition, 2022)
This study described the quality and microbial influence on ozone water (OW) and ultra-high pressure (UHP) processing alone or in combination with refrigerated catfish fillets. The analysis parameters included total volatile base nitrogen (TVBN), thiobarbituric acid reactive substances (TBARs), chromaticity, microbial enumeration, 16S rRNA gene sequencing, electronic nose (E-nose), and sensory score. The study found that compared with the control (CK), ozone water combined with ultra-high pressure (OCU) delayed the accumulation of TVBN and TBARs. The results of sensory evaluation illustrated that OCU obtained a satisfactory overall sensory acceptability. The counting results suggested that compared to CK, OCU significantly (p < 0.05) delayed the stack of TVC, Enterobacteriaceae, Pseudomonas, lactic acid bacteria (LAB), and hydrogen sulfide-producing bacteria (HSPB) during the storage of catfish fillets. The sequencing results reflected that the dominant were Proteobacteria, Firmicutes, Bacteroidetes, and Actinobacteria at the phylum level, and the dominant were Acinetobacter, Pseudomonas, Lelliottia, Serratia, Shewanella, Yersinia, and Aeromonas at the genus level. The dominant was Acinetobacter in initial storage, while Pseudomonas and Shewanella were in anaphase storage. Based on the TVC and TVBN, the shelf life of catfish fillets was extended by at least 3 days compared to the control. In short, the combination of ozone water and ultra-high-pressure processing is a favorable strategy to control microbial quality and delay lipid oxidation during catfish storage.